Definitive Nasalsilicone Material Prosthesis To Replace The Nose Lost In Post Total Rhinectomy Patient: Case Report - Endang Prawesthi; Dany Riady (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Patients with loss of nasal anatomy effect surgical defects after total rhinectomy, often feel shame and less 0f confident to socialize with the people around. The defect due to loss of the nose can be repaired by nasal prosthesis. This nasal protesa is generally made by using flexible materials such as silicone. Silicone type room temperature vilcanitation (RTV) material is a silicone material often used because it is easy to manufacture, has good physical properties that is more adaptable to the skin and can be used in the long term. The purpose: to determine the stages and problem solving of the difficulties that arise in the procedure of fabricating definitive nasal prosthesis with RTV silicone material. The method is based on working model done in dental laboratory, starting from the preparation of work model, night pattern making, duplicate work model, flasking, boiling out, silicone application, curing, deflasking, finishing prosthesis. The results obtained by the prosthesis with the basic color and still require further staining, the natural anatomical form and in accordance with the working model although there is little porous in some places. Conclusion: the fabrication of nasal prostheses with RTV silicone material can be done with good results with anatomical form and texture that are almost identical to the original nose, but there is a shortage of the prosthesis can not be repaired in case of fault during the fabricating process